The reported effects of the COVID-19 pandemic on people with intellectual disability and their carers: a scoping review - Owen Doody; Paul M. Keenan (Annals of Medicine)
Background People with an intellectual disability are a vulnerable group during COVID-19 due to multi-morbidity, frailty, underlying conditions/health problems, social circumstances and limitations in understanding. This places them at greater risk of more severe outcomes from COVID-19.Objective To chart the evidence of the effects of the COVID-19 pandemic on people with intellectual disability and their carers reported in the research.Methods A scoping review method was used to review literature published across eight databases in 2020 and included manual searches of reference lists of included articles.Results Sixteen studies were selected for inclusion. The findings highlight that professionals, people with intellectual disability and their carers were keen to comply with pandemic related public health guidance. However, implementing infection prevention and control measures in certain contexts for people with intellectual disability was challenging. Thereby a rights-based, person-centred approach to care is essential and professionals need to extend their understanding and practice of collaborative working to include people with intellectual disability and their family/carers. The findings highlight that compliance with public health guidance and infection control measures can be difficult for people with intellectual disability to implement.Conclusions There is limited good quality robust research on COVID-19 and people with intellectual disability and/or their carers experiences.